Cross pathogenicity of Verticillium spp. isolated from different hosts - ZHANG Yuanyuan; ZHANG Gui; ZHANG Jian; ZHANG Guang; ZHOU Hongyou; ZHAO Jun (浙江大学学报. 农业与生命科学版)
Verticillium spp. is a group of soil- borne pathogen causing a yellow wilt disease on different kinds of hosts, such as cottons, potatoes, sunflowers and egg-plants, etc. So far, Verticillium dahliae and Verticillium alboatrum have been the most dominant species isolated from different diseased hosts.In this study, V. dahliae from sunflower, cotton, eggplant, lettuce and potato and V. alboatrum from potato were selected to study the colonial morphology, growth speed, and pathogenic specificity. Their race and mating types were also identified by specific primers.The results showed that variable colonial morphology and growth speed were observed in all the tested isolates. Four different kinds of colonial morphologies were classified based on the amount of aerial mycelium and the number of microsclerotia. However, the difference on the morphology of conidiophores and conidia was not obvious among all the tested isolates. The growth speed was also variable after 10 d of culture on potato D-glucose agar (PDA) medium. The strain Ls17-6 from lettuce grew the fastest, while Hn-1 from cotton grew the slowest. The difference of growth speed was also observed among the isolates obtained from the same host. For example, Hn-1 isolated from cotton was significantly lower compared with the other two isolates. All the tested isolates were characterized as race 2, except for Ls16-1 isolated from lettuce as race 1; the mating type of all the tested strains was MAT1-2-1. The pathogenic specificity was studied using root dipping inoculation way. Twenty- one days post- inoculation (dpi), the pathogenicity of isolates always showed the highest virulence on its own host. For example, Sx5 which was isolated from sunflower showed the highest disease index of 52.50, followed by the isolate V991 from cotton with the disease index of 41.25. The same result was also obtained on cotton. For example, the isolate V991 showed the highest pathogenicity, and Icd3-33 also from cotton listed in the second position among all the tested isolates.In conclusion, the pathogenicity of Verticillium spp. on the different hosts is variable, but shows the strongest pathogenicity in the specific host. Besides, the isolates from lettuce always showed the lowest virulence on all the tested hosts, indicating lettuce may be used as a rotation host for other crops to control the yellow wilt in the future.